PS02.052: AUTO-ANTIBODIES AGAINST TUMOR ANIGENS ARE USEFUL BIOMARKERS IN PATIENTS WITH ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (14th September 2018) - Shimada, Hideaki; Yajima, Satoshi; Oshima, Yoko; Ito, Masaaki; Nanami, Tatsuki; Suzuki, Takashi; Funahashi, Kimihiko; Otsuka, Seiko; Hoshino, Isamu; Nabeya, Yoshihiro
Abstract: Background: Serum antibodies are induced even ata the eraly phase of carcinogenesis. Serum p53 antibodies (s-p53-Abs) have been developed and approved as routine blood test for monitoring esophageal squamous cell carcinoma (SCC). Recently, we have developed new ELISA systems to detect serum anti-IgG auto-antibodies against tumor antigens in patients with esophageal (SCC). In this paper, we focused on serum auto-antibodies against p53, NY-ESO-1, Galectin-1 and RalA. Methods: Serum samples of patients with esophageal SCC were obtained before surgery. Serum anti-IgG antibodies against several tumor antigens were analyzed by newly developed ELISA systems. Target tumor antigens were p53, NY-ESO-1, Galectin-1 and RalA. Cut-off values were fixed using mean + 3SD of values of a total of 74 healthy controls. Changing pattern of serum p53 antibodies titers was also assessed during postoperative follow-up. Results: Positive rates of serum antibodies were 18% for p53, 31% for NY-ESO-1, 10% for Galectin-1 and 9% for RalA. Positive rates of these antibodies in healthy controls were 0%. Combination assay improved positive rates without increased false positive rates as follows; p53 + NY-ESO-1 = 40%, p53 + NY-ESO-1 + Galectin-1 = 47%, p53 + NY-ESO-1 + Galectin-1 + RalA = 51%. Although some patients with extremely-high antibody titer for p53 persistently positive even after curative surgery, changing patterns of serum titers seemed to be associated with clinical outcome. Conclusion: Although antibody titer of s-p53-Abs seemed to be associated with tumor burden, the titer gradually decresed at the last several months of the terminal stage. Such independent changing pattern of serum autoantibodies may have adding information to conventinal serum markers. We have developed new ELISA system to detect serum autoantibodies for patients with esophageal SCC. Although the positive rates of single serum auto-antibody were still relatively low, combination assay with plural auto-antibodies may be useful. Disclosure: All authors have declared no conflicts of interest.